Recent advances on the functional and evolutionary morphology of the amniote respiratory apparatus. Issue 1 (February 2016) - Lambertz, Markus
Abstract : Increased organismic complexity in metazoans was achieved via the specialization of certain parts of the body involved in different faculties (structure–function complexes). One of the most basic metabolic demands of animals in general is a sufficient supply of all tissues with oxygen. Specialized structures for gas exchange (and transport) consequently evolved many times and in great variety among bilaterians. This review focuses on some of the latest advancements that morphological research has added to our understanding of how the respiratory apparatus of the primarily terrestrial vertebrates (amniotes) works and how it evolved. Two main components of the respiratory apparatus, the lungs as the "exchanger" and the ventilatory apparatus as the "active pump, " are the focus of this paper. Specific questions related to the exchanger concern the structure of the lungs of the first amniotes and the efficiency of structurally simple snake lungs in health and disease, as well as secondary functions of the lungs in heat exchange during the evolution of sauropod dinosaurs. With regard to the active pump, I discuss how the unique ventilatory mechanism of turtles evolved and how understanding the avian ventilatory strategy affects animal welfare issues in the poultry industry.